"The Penny Lunch has Spread Faster than the Measles": Children's Health and the Debate over School Lunches in New York City, 1908–1930. Issue 2 (May 2015) - Ruis, A. R.
Abstract : A few days before Thanksgiving in 1908, the home economist Mabel Hyde Kittredge initiated a school lunch program at an elementary school in Hell's Kitchen, serving soup and bread to hungry children in the infamous Manhattan neighborhood. The following year, she founded the School Lunch Committee (SLC), a voluntary organization composed of home economists, educators, physicians, and philanthropists dedicated to improving the nutritional health and educational prospects of schoolchildren. By 1915, just seven years after the initiative began, the SLC was serving 80, 000 free or low-price lunches a year to children at nearly a quarter of the elementary schools in Manhattan and the Bronx. Most of the schools were located in the city's poorest districts, and experience showed that the lunches were reaching those most in need at minimal cost to the organization. All the food served was inspected by the Health Department, and the meals were nutritionally balanced and tailored to the ethnic tastes and religious requirements of different school populations. Sparse but compelling evidence indicated that the program had reduced malnourishment among the children who partook, and teachers and principals at participating schools reported reductions in behavioral problems, dyspepsia, inattentiveness, and lethargy.